Diffusion Tensor MR Imaging and Comparative Histology of Glioma Engrafted in the Rat Spinal Cord - Inglis, Ben A.; Neubauer, Debbie; Yang, Lei; Plant, Dan; Mareci, Thomas H.; Muir, David (American Journal of Neuroradiology, 1999)
Summary: MR imaging using contrast material derived from the diffusion of tissue water was tested for its ability to provide a nondestructive histologic analysis of tumor morphology. An apparent diffusion tensor MR image of a glioma engrafted within a rat spinal cord was generated in which fiber orientation in three dimensions was displayed in color. This imaging method clearly separated tumor from host white and gray matter and corresponded well with conventional histologic microscopy.